ANALYZING CASSAVA PROCESSORS’ PREFERRED OUTPUT AND PROFITABILITY OF CASSAVA PROCESSING IN HOHOE MUNICIPALITY - Musah, S.; Kwakye, E.; Kudaddze, S.; Adzawla, W. (UDS International Journal of Development, 2020)
Cassava is one of the most perishable tuber crops, and to prevent postharvest losses cassava processing is an essential component of the cassava value chain. This study analyzed the preferred output forms of the cassava processors and the profit margins of the various output forms. This was done in the Hohoe municipality of the Volta Region, Ghana. A total of 135 respondents were selected through a multistage sampling procedure and interviewed through the use of structured questionnaires. The data was analyzed using Stata version 17 and SPSS version 23. The various output derived from cassava are dough, gari and pellets. From the result, the most preferred output was cassava dough (93.1%) while the most profitable cassava processing venture is gari (93.8%) processing. The factors that significantly influenced the profitability of dough were age, educational level, cassava farm size, experience, cassava source, contract on dough, dough purpose, price per bag (25kg) of dough, training in dough processing and a price of dewatering. The result also showed crosscutting challenges such as labour intensive, difficulty in drying cassava chips, unstable market and time consuming. Opportunities for cassava processing into various forms are ready market for the products. The study concluded that to increase the returns from cassava processing, processors are encouraged to process cassava into gari other than pellet or dough. The study also recommended that technological advancement on gari processing should be promoted to make the activity less labourious and difficult. Keywords: Cassava Processing, Hohoe Municipality, Multiple Linear Regression, Preferred Output, Profitability